Self-Esteem Dan Pelayanan Bimbingan Dan Konseling yang Dibutuhkan Siswa Kelas Akselerasi - Yendi, Frischa Meivilona; Syukur, Yarmis; Rafsyam, Yusri (Konselor, 2015)
The research purpose to describe: 1) self-esteem of acceleration students, 2) the guidance and counseling service required by acceleration students. Research methods used are descriptive quantitative. Research subject represent class student of XI dan XII CI/BI senior high school 1 of Padang which amount to 48 people. Result of reseacrh show that self-esteem of acceleration students high in general, consist of general self-esteem, social self-esteem and personal self-esteem. Requirement of acceleration students tothe guidance and counseling service are in general very high, consist of orientation service, information service, location service and channeling, domination of konten service, individual counseling service, group guidance service, group counseling service, consultancy service and also service of mediasi.